F(x) = x^2 - 3x - 7
f(-3) = (-3)^ 2 - 3(-3) - 7
f(-3) = 9 + 9 - 7
f(-3) = 18 - 7
f(-3) = 11
Answer:
x = 9, Angles are 54°
Step-by-step explanation:
First, we need to find x:
7x-9 = 5x+9
+9 +9
7x = 5x+18
-5x -5x
2x = 18
x = 9
Now, we plug our x value in to find our angles.
5(9) + 9 = 54
Angle B = 54°
7(9) - 9 = 54°
Angle E = 54°
(angles are the same due to AAA property)
Answer:
A 2/6 and 3/6 is the Answer
Answer: 40 pounds of cashews should be mixed with the peanuts to ensure no change in the revenue
Step-by-step explanation:
Let x represent the number of pounds of cashews that should be mixed with the peanuts to ensure no change in the revenue.
The nut store normally sells cashews for $4.00 per pound and peanuts for $1.50 per pound.
In order to sell 60 pounds of peanuts, the manager decided to mix the 60 pounds of peanuts with some cashews and sell the mixture for $2.50 per pound. It means that
4x + (1.5 × 60) = 2.5(60 + x)
4x + 90 = 150 + 2.5x
4x - 2.5x = 150 - 90
1.5x = 60
x = 60/1.5
x = 40
Answer:
Step-by-step explanation:
Anything raise to the power zero is 1
Therefore,
![LHS\\\\ =2^3 \times 3^0 + 3^2 \times 2^0\\\\8 \times 1 + 9 \times 1 \\\\17](https://tex.z-dn.net/?f=LHS%5C%5C%5C%5C%20%3D2%5E3%20%5Ctimes%203%5E0%20%2B%203%5E2%20%5Ctimes%202%5E0%5C%5C%5C%5C8%20%5Ctimes%201%20%2B%209%20%5Ctimes%201%20%5C%5C%5C%5C17)
LHS = RHS
Hence Proved